Pendekatan Evidence Based Oral Hygiene dengan Kassa dan Spons yang Mengandung Chlorhexidin 2% dalam Pencegahan Ventilator Associated Penumonia - Nazhifa Nida Iftina; Erina Adriana Paramitha; Amaliah Mahmudah; Sri Rahayu; Endar Sulistyo (Journal of Telenursing (JOTING), 2026)
This study aimed to analyze the differences in effectiveness of oral hygiene measures using gauze and sponges containing 2% chlorhexidine in preventing Ventilator-Associated Pneumonia (VAP) in patients on mechanical ventilation in the ICU. A literature search was conducted through PubMed, ScienceDirect, Scopus, Google Scholar, and GARUDA databases for national and international articles published between 2017 and 2025. Seven articles that met the inclusion and exclusion criteria were systematically analyzed. The results of the literature review indicated that oral hygiene using sponges containing 2% chlorhexidine tended to be more effective than gauze in reducing oral bacterial colonization and preventing VAP. These findings suggest that selecting appropriate oral hygiene devices, along with the use of effective antiseptics, is an important component of evidence-based critical care nursing practice to reduce the risk of Ventilator-Associated Pneumonia in ICU patients.   Keywords: Chlorhexidine 2%, Gauze, Oral Hygiene, Sponge, Ventilator-Associated Pneumonia